Memory and the teaching of the history of drugtraficking and the emerald wars. The socio-cultural value of narcorrido. - Almonacid Buitrago, Julián Alveiro; Burgos Dávila, César Jesús (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The aim of this article is to analyze the practice of the teaching of history in secondary school, as regards the violence, the wars over emeralds and the drug traficking in the province of Rionegro, Colombia. Classwork was carried out based on an ethnographic method with the proposal of double relexivity, the teaching of history with memory and the techniques of observation-insertion. Narcorridos were used as a didactic resource to create a historical consciousness through the remembrance of speciic conlicts. The results were organized into three categories: a) the function of narcorridos as living memory and its didactic value; b) communicative memory and every-day musical environments; c) other places of memory. Narcorridos offer alternative social memories for the teaching of history in Colombia, which help in the construction of a historical sense, favor the understanding of the post-conlict situation and the generation of peace in the territory.